A first preliminary study of the sponge fauna associated to white coral banks from the Alboran Sea - Gabriele Costa; Marzia Bo; Jordi Grinyó; Claudio Lo Iacono; Maurizio Pansini; Marco Bertolino (2018)
The scleractinians Madrepora oculata and Lophelia pertusa form, in deep water, three-dimensional structures which allow the settlement of a rich sponge community. The analysis of a white coral block with a surface area of about 360 cm2, collected between 306 and 354 m depth from the Alboran Sea during the campaign MELCOR of 2012, allowed to identify 19 sponge species. Sixty-six sponge specimens (demosponges and hexactinellids), associated to white corals were collected in total. Sponge samples may be attributed to the species, Hymerhabdia oxytrunca Topsent, 1904, Hymerabdia sp., Acantheurypon pilosella (Topsent, 1904), Monocrepidium vermiculatum Topsent, 1898, Desmacella infundibuliformis (Vosmaer, 1885), Haliclona (Gellius) bioxeata (Boury-Esnault, Pansini & Uriz, 1994), Haliclona (Gellius) lacazei (Topsent, 1893), Haliclona (Reniera) cratera (Schmidt, 1862), Damiria curvata (Vacelet, 1969), Discorhabdella hindei Boury-Esnault, Pansini & Uriz, 1992, Anisocrella hymedesmina Topsent, 1927, Crella (Pytheas) alba (Vacelet, 1969), Hymedesmia (Hymedesmia) gracilisigma Topsent, 1928, Hymedesmia (Hymedesmia) zetlandica Bowerbank, 1864, Plocamionida ambigua (Bowerbank, 1866), Latrunculia (Biannulata) citharistae Vacelet, 1969, Podospongia lovenii Barboza du Bocage, 1869, Vulcanella gracilis (Sollas, 1888) and, Tretodictyum tubulosum Schulze, 1886. Haliclona (Gellius) bioxeata and Hymerhabdia oxytrunca, with over 20 specimens collected, are the most abundant species. Thirteen species are new findings for the white coral assemblage, one is a new finding for the Mediterranean Sea and a species of Hymerabdia is probably new for science. As to biogeography most of the species (53%) have atlantic-mediterranean distribution, 5% are only atlantic and 42% are Mediterranean endemics. This is the first survey of sponges associated to deep coral reefs in the Alboran Sea and confirms that these habitats are hot spots of biodiversity on deep grounds.